Vörösmarty könyvkiadási gyakorlatának néhány jellemzője - Gere, Zsolt (Studia Litteraria, 2021)
The literary publishing practices related to Mihály Vörösmarty are among the least well-researched subjects of the author’s oeuvre, even though Vörösmarty himself was hoping for a substantial amount of his income to come from this source. This paper aims to focus on three major questions regarding Vörösmarty’s publications: did the published texts garner any substantial income, and did it affect his way of life in any way; what sort of funding was chosen by him (subscriptions, stakeholders, etc.); and on what genres was he focusing most intensely? In conclusion, the paper also focuses specifically on the question of whether the establishment of the Pesti Magyar Színház (Hungarian Theater of Pest), otherwise known as Nemzeti Színház (National Theater) and the staging of his dramatic works brought about any changes in these former practices.